Perubahan Paradigma Strategi Deterensi Nuklir India dan Pakistan - Rossdiana, Renatha Ayu (Andalas Institute of International Studies UNAND, 2023)
This paper discusses the shifting in the nuclear deterrence strategies of India and Pakistan. The conflict between India and Pakistan is marked by several high tension such as Kashmir dispute. The presence of nuclear weapons, which is pretty much significant and balanced possession between India and Pakistan make the situation more complicated and challenge the political stability in South Asia. The deterrent strategy of both parties has shifted from full deterrence, where nuclear ownership is to deter the opposing party, to creating second-strike and pre-emptive strike capabilities because they feel an increase in potential threats. India applies the no-first-use (NFU) doctrine, which was initially quite strict but has now become flexible considering the threat from Pakistan. Meanwhile, Pakistan tends to be a risk-taker by never declaring the NFU doctrine. The author uses nuclear deterrence theory and security dilemma to elaborate the shifting concept of a deterrent strategy by both parties. The rationality of both parties in nuclear deterrence must be the basis of nuclear doctrine, considering the massive impact if both sides engage in a nuclear war. Globally, there needs to be cooperation in mutual control not only in nuclear-armed countries but also in diplomacy among countries that do not have nuclear powers to create global peace. At least in the event of war, both countries do not use their nuclear power.